Effect of planting method and spacing on growth, yield and fruit characteristics of papaya fruit (Carica papaya L.) - S. Osman, Mohamed; M. Elamin, Osman; E. Elkashif, Mohamed (Gezira Journal of Agricultural Science, 2023)
Field experiments were conducted at the experimental farm of the Faculty of Agricultural Sciences, University of Gezira, Wad Medani, Sudan, during 2007-2009. The objective was to study the effects of plant spacing and planting method on vegetative growth, number of days to flowering, number of days from flowering to harvesting, yield and fruit characteristics of two papaya cultivars. Papaya cultivars used were “Baladi” and “Solo”. Spacings used were 1.5X2 m, 2X2 m and 2 X 2.5m and the methods of planting were beds and flats. Treatments were arranged in a randomized complete block design with three replicates. Results showed that cultivars, plant spacing and method of planting had significant effects on papaya vegetative growth, flowering, yield and fruit characteristics. “Solo” cultivar showed more vigorous vegetative growth, more  number of days to first flowering, less number of days from flowering to harvesting and produced more fruits per tree. However, the “Baladi” cultivar produced large fruits and high yield per ha. Plant spacing of 2X2.5 m and the bed planting method resulted in the best vegetative growth and yield as compared to the other treatments in both seasons.